2007
DOI: 10.1117/12.716823
|View full text |Cite
|
Sign up to set email alerts
|

The slow-flow method of identification in nonlinear structural dynamics

Abstract: The Hilbert-Huang transform (HHT) has been shown to be effective for characterizing a wide range of nonstationary signals in terms of elemental components through what has been called the empirical mode decomposition. The HHT has been utilized extensively despite the absence of a serious analytical foundation, as it provides a concise basis for the analysis of strongly nonlinear systems. In this paper, we attempt to provide the missing link, showing the relationship between the EMD and the slow-flow equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, the use of HHT for nonlinear system identification is still in its early stage [14][15][16][17]. Tasks of nonlinear system identification include (1) detection of the existence and spatial locations of nonlinearities, (2) determination of the types, orders, and functional forms, and (3) identification of system parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of HHT for nonlinear system identification is still in its early stage [14][15][16][17]. Tasks of nonlinear system identification include (1) detection of the existence and spatial locations of nonlinearities, (2) determination of the types, orders, and functional forms, and (3) identification of system parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In several earlier papers, the authors demonstrated a relationship between Intrinsic Mode Functions (IMFs), derived from the Empirical Mode Decomposition (EMD), and the slow-flow model of a strongly nonlinear dynamical system 1,2,3 . This naturally led to the development of the Slow Flow Model Identification (SFMI) method for strongly nonlinear systems, in which the physical parameters of such systems could be identified from experimental data.…”
Section: Introductionmentioning
confidence: 99%